Race, class and Christianity in South Africa: middle-class moralities - Abraham, Ibrahim (Routledge studies on religion in Africa and the diaspora, 2022)
Introduction: Day Zero in Cape Town -- Christianity and the middle class in South Africa -- Middle-class morality and Christianity in South Africa -- Spiritual and class insecurity in South Africa -- Middle-class moral insecurity in South Africa -- Race, class, and habitus in South African churches -- Anomie and vocation in South African Christian ministry -- Musicking, unity, and sincerity in South African churches -- Conclusion: Covid-19 in Cape Town.